PSYCHOLOGICAL-PEDAGOGICAL CONDITIONS OF THE IMPROVEMENT OF MEDICAL STUDENTS LEVEL OF KNOWLEDGE - O. M. Kolomiets; M. A. Fokina; E. S. Egorova (Сеченовский вестник)
The article covers the problem of students’ professional activity training in the Higher Medical School and psycho-pedagogical conditions of their learning activity on the basis of the systems and activity approach. The article describes a new pedagogical means — “the activity reference scheme”, presenting the material of all theoretical and practical disciplines as the integral system with its structure and contents. The article tells about students’ professional activity training, organized on the basis of “the activity reference scheme” of system type, that develops clinic (system) thinking.